2010
DOI: 10.1166/jnn.2010.2080
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Fluorescence from CdTe Quantum Dots Self-Assembled on the Surface of Silver Nanoparticles

Abstract: This paper presents an investigation on the fluorescent properties of semiconductor CdTe quantum dots (QDs) self-assembled on the surface of PVP (polyvinylpyrrolidone)-capped silver nanoparticles (NPs) by the ligand field effect. A significant 2.5-fold enhancement in the integrated fluorescence intensities, red shift of fluorescence peak, and obvious decrease of lifetime were observed in the CdTe QDs assembled on the Ag NPs in comparison with the pure CdTe QDs. The fluorescence enhancement factor and red shift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…268 In addition, a range of different fluorophore based experiments have been conducted including carbon nanotubes, 269 hypericin, 260,261 chlorophyll, 270 phycobiliproteins, 258 RNA, 257 fluorescein-labeled oligonucliotides, 255,256 and recently, a dynamic observation of protein translation has been reported. 271 Interestingly, it has also been reported that PL of QDs at the surface of metallic NPs can also be enhanced, [272][273][274][275] opening up the possibilities for rationally designed plasmonic/QD PL probes with enhanced emission.…”
Section: Metallic Surface Enhanced Fluorescencementioning
confidence: 99%
“…268 In addition, a range of different fluorophore based experiments have been conducted including carbon nanotubes, 269 hypericin, 260,261 chlorophyll, 270 phycobiliproteins, 258 RNA, 257 fluorescein-labeled oligonucliotides, 255,256 and recently, a dynamic observation of protein translation has been reported. 271 Interestingly, it has also been reported that PL of QDs at the surface of metallic NPs can also be enhanced, [272][273][274][275] opening up the possibilities for rationally designed plasmonic/QD PL probes with enhanced emission.…”
Section: Metallic Surface Enhanced Fluorescencementioning
confidence: 99%
“…The excitonic peak in case of Ag-nCdTe colloid also got bleached compared to the bare CdTe QD colloid. Various groups have reported similar changes in the extinction spectrum in metal-semiconductor HNS when compared to that of individuals [18][19][20][21][22] . The increase in the absorption cross-section in the longer wavelength of Ag-nCdTe is attributed to the defect states created by the attachment of Ag NP to CdTe QD.…”
Section: Resultsmentioning
confidence: 81%
“…The extinction spectra of the H AgP T colloid looks more like that of CdTe QD but with two modified features, (i) the bleaching of the exciton peak at around 2.21 eV and (ii) band tailing at the lower energy side below 2 eV. Bleaching of exciton peak in the presence of MNP has been attributed to exciton dissociation in the presence of high electric fields 40,41 . On the other hand the band tailing below 2 eV is also observed in several other metal-semiconductor HNS and has been attributed to the formation of additional surface defect states 42 .…”
Section: Resultsmentioning
confidence: 97%